Konsentrasi Ekstrak Etanol Kulit Buah Kakao (Theobroma cacao L.) dan Suhu Pemanasan terhadap Karakteristik Krim Body Scrub - Rahayu, Erna Sri; Wartini, Ni Made; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
Cocoa pod husk extract can be used as a source of antioxidants in cosmetic preparations, namely cream body scrub. Cream body scrub is a type of cosmetic cleanser that is used to clean dead skin cells and nourish the skin. This study aims to (1) know the effect of the concentration of ethanol extract of cocoa pod and heating temperature on the characteristics of cream body scrub and to (2) determine the concentration of ethanolic extract of cocoa pod and the best heating temperature to produce cream body scrub. This study used a factorial randomized block design with two factors. The first factor is the concentration of the extract which consists of 3 levels, namely 1%, 2%, and 3%. The second factor is the heating temperature which consists of 2 levels, namely 65±2°C and 75±2°C. The results showed that the concentration of the extract and the heating temperature and their interactions affected the antioxidant capacity, antioxidant activity, pH, viscosity, spreadability, color, aroma and overall acceptance. Extract concentration of 3% and heating temperature of 65±2°C is the best treatment to produce cream body scrub with antioxidant capacity characteristics of 85.02±0.22 mg GAEAC/g, antioxidant activity 98.48±0.82 ppm (strong antioxidant), pH 6.66±0.02, viscosity 34200±200 cp, spreadability 4.78±0.10 cm, sensory evaluation: color 4.35±0.48(light brown to light brown), aroma 6.25 ±0.71 (fairly typical of cocoa to typical of cocoa) and overall acceptance of 6.25±0.71(like to very like). Keywords: cocoa pod husk, concentration, temperature, characteristics, cream body scrub.